An experimental investigation of the bicycle motion during a hands-on shimmy. Issue 9 (2nd September 2021) - Tomiati, Nicolò; Magnani, Gianantonio; Marcon, Marco
Abstract : This paper presents original data records of linear accelerations and angular velocities of six points of a racing bicycle collected during a 'genuine' hands-on shimmy. The records, together with GPS, forward speed data, and action cam videos are thoroughly analysed to understand the actual motion of the bicycle and its parts, at lower (weave) and higher (wobble or shimmy) frequencies. The main goal is to assess how and to what extent each part, and what compliances, are involved in the shimmy mechanism. In particular, the motions of the front and rear frames, and thus of the whole bicycle, during shimmy are carefully rebuilt. At higher frequencies, the rear frame rotates rigidly about an axis parallel to the yaw axis, while it undergoes a relative torsion between the head tube and the dropouts in the longitudinal (roll) direction. Likewise, the front frame rotates rigidly about the steering axis (in the entire frequency range), while it bends laterally consistently with the rear frame torsion. Although the overall motion is very complex, these results validate and extend models, conjectures, and theoretical results of the scientific literature about shimmy.